Two mechanisms of soluble CD4 (sCD4)-mediated inhibition of human immunodeficiency virus type 1 (HIV-1) infectivity and their relation to primary HIV-1 isolates with reduced sensitivity to sCD4. - Orloff, S L (1993)
Two assays for measuring inhibition of human immunodeficiency virus type 1 (HIV-1) infection by soluble CD4 (sCD4) are described. Experiments in which sCD4, HIV-1, and cell concentrations and sequence of combination, noninfectious/infectious particle ratio, and temperature were varied produced results that support the conclusion that sCD4 inhibits HIV-1 infection by two mechanisms: reversible blockage of receptor binding and irreversible inactivation of infectivity. Fresh isolates obtained from HIV-1-infected persons were tested in both assays and found to be more resistant to both mechanisms of sCD4-mediated inhibition than multiply passaged laboratory strains. Binding studies revealed similar affinities for sCD4 in detergent lysates of sensitive and resistant strains at both 4 and 37 degrees C. The avidity of intact virions for sCD4 was lower at 4 than at 37 degrees C, and in the presence of excess sCD4, less sCD4 was bound at 4 than at 37 degrees C. The avidity differences were similar for fresh isolates and laboratory strains. However, fresh isolates were more resistant to sCD4-induced shedding of envelope glycoprotein gp120 from intact virions than was the laboratory strain. Relative resistance to sCD4 by certain isolates does not represent a lower intrinsic affinity of their envelope for sCD4 or a lower capacity for sCD4 binding. Rather, an event that occurs after binding may account for the differences. This postbinding event or feature may be determined by regions of the envelope outside the CD4 binding site.